How to design a financial market experimentation: The qualitative approach - Finet, Alain; Kristoforidis, Kevin; Laznicka, Julie (International Journal of Social and Administrative Sciences, 2025)
This article aims at strengthening financial literature by providing a qualitatively inspired experimental protocol for analyzing the influence of emotions and cognitive and behavioral biases on the decision-making of individual investors. Most studies in this field generally rely on a quantitative approach, which is restricted to demonstrating cause-and-effect relationships based on large sample sizes, without actually analyzing the psychological reality of individual investors. Consequently, the literature shows a growing interest in the use of qualitative methodologies to better understand the financial decision-making process. However, laboratory experimentation must be based on a well-designed experimental protocol, so that other researchers can replicate the experiment with a precise understanding of the set-up and conditions. Accordingly, this article details the fundamental principles of experimental protocol design, based on existing literature. We then propose the practical set-up of an experiment on financial markets, using qualitative tools such as questionnaires, semi-directive interviews and a focus group. The article demonstrates the advantages of the qualitative approach in understanding the emotional and cognitive influence on the decision-making process. This methodology and the protocol offer a more precise analysis of people’s psychological reality, often ignored by quantitative approaches.